Influence of organic fertilisation on leaves and essential oil production of Ocimum gratissimuim L. - Chaves, FCM; Ming, Lin Chau [UNESP]; Ehlert, PAD; Fernandes, Dirceu Maximino [UNESP]; Marques, MOM; Meireles, MAA (International Society Horticultural Science, 2002)
The experiment was installed in Lageado Experimental Farm with aim to verify the influence of organic fertilisation (0, 4, 8 and 12 kg of manure/m(2) - with four replications) on leaves and essential oil production of Ocimum gratissimum. The harvesting was done twice (May - autumn and August - winter), and the leaves were separated for extraction of essential oil by Clevenger apparatus. The leaf production and oil content were calculated on dry mass basis. The results showed no statistical difference for organic fertilisation, although significant difference was verified for seasons. The main constituents of essential oil were eugenol and 1,8- cineole. The amount of the eugenol was higher in autumn, while the presence of other components including 1,8-cineole, beta-selinene and trans-caryophyllene were more dominant at wintertime.
Keywords: oil content; eugenol; 1,8-cineole; beta-selinene; trans-caryophyllene